1994
DOI: 10.1007/bf00327161
|View full text |Cite
|
Sign up to set email alerts
|

CMV-induced class II antigen expression in various rat organs

Abstract: Cytomegalovirus (CMV) is thought to trigger acute or chronic allograft rejection by inducing the expression of MHC class II antigens in the graft. This induction may be mediated by gamma-interferon or directly by CMV. In this study, we have investigated which structures in the rat kidney, liver, and heart are responsive to CMV-induced class II expression in vivo. Rats were infected with rat CMV, the organs were harvested during the acute phase of infection, and the virus was demonstrated by culture from each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…However, it is consistent with previous studies indicating that rat endothelium does not express MHC class II constitutively,20 but expression can be induced in retina, brain, liver, kidney21,22 and on heart allotransplants23 by immune upregulation.…”
Section: Discussionsupporting
confidence: 93%
“…However, it is consistent with previous studies indicating that rat endothelium does not express MHC class II constitutively,20 but expression can be induced in retina, brain, liver, kidney21,22 and on heart allotransplants23 by immune upregulation.…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies have also demonstrated persistence of CMV DNA in bile duct epithelium and endothelial cells of grafts with chronic rejection (19). CMV may have a direct effect on infected cells and an indirect immune effect associated with enhanced expression of HLA antigens and adhesion molecules on biliary and endothelial cells (20). This might explain why CMV precedes LAR as shown in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that R33 is essential for virus replication in salivary glands is also supported by the inability to detect class II MHC expression in the salivary gland epithelium of RCMV⌬R33-infected rats. Class II MHC expression is evoked by RCMV infection of rat heart endothelium (50), liver and kidney cells (51), and salivary gland epithelium (Fig. 10).…”
Section: Discussionmentioning
confidence: 99%